Historical ruins – between conservation doctrine and social acceptance - Andrzej, Siwek (Protection of Cultural Heritage, 2020)
From the doctrinal take, ruin is perceived as a full-fledged historical monument representing autonomous values. Highly polemic against the doctrine and theory is the practice expressed in concrete interventions in the substance and surroundings of a historical monument. It can thus be stated that the entire post-war period was one of affirmation and praise of the Rebuilding/Reconstruction/Restoration project. The Rebuild slogan has taken root as a positive and creative idea. In order to implement the doctrinal concept of the protection of ruins, there is a purpose behind restoring the social skill of perceiving the beauty of historical ruins as signs in the landscape. And, there is a purpose in educating the community in terms of to what extent ruins, without a useful function of their own, may be useful or useable anyway – as a regional attraction, a imagination-inspiring magnet attracting tourists. This poses a considerable challenge to experts in cultural goods protection: not only should they demonstrate an in-depth recognition of restoration/conservation doctrines but also render themselves acquainted with information, educational, and negotiation techniques – in order to contribute to the decisions regarding the lot of historical monuments, historical ruins in particular.